Pengaruh Pertumbuhan Benih Ikan Mas (Cyprinus carpio) Dengan Pemberian Pakan Kombinasi Pellet Dan Lemna (Lemna perpusilla) Di Balai Benih Ikan Kabupaten Langkat Kecamatan Bahorok - Selfiana Selfiana; Kartika Manalu; Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
This investigation means to decide the impact on the development of goldfish seeds when taken care of pellets, to decide the impact on the development of goldfish seeds when taken care of with Lemna, and to decide the impact on the development of goldfish seeds when taken care of with a blend of pellets and Lemna. The exploration was directed from March - June 2020, at the Fish Seed Center, Bahorok District, Dusun VI, Timbang Jaya Village. Taking care of treatment A (100% pellets without giving lemna), Treatment B (75% pellets and 25% lemna), Treatment C (25% pellets and 75% lemna), Treatment D (half pellet feed and half lemna), Treatment E (100% lemna without pellets). The outcomes showed that the mix of pellet and lemna feed with a proportion of half pellets and half lemna significantly affected outright development, supreme weight, every day development rate, feed transformation rate, endurance rate, and water nature of goldfish (Cyprinus carpio).